Tingkat Keterbacaan Pada Buku Teks Bacaan “English For Nusantara” Yang Digunakan Pada SMP Kelas Tujuh - Utami, Wahyu (EduCurio: Education Curiosity, 2023)
This research aims to determine the readability level of reading texts and the readability class of reading texts in English books with the title "English for Nusantara" for class VII. The method used in this research is a descriptive research method with a quantitative approach. Researchers measured the level of readability of reading texts in the book "English for Nusantara" using the Flesch Reading Ease and Flesch Kincaid Reading Age formulas. Researchers measured 11 reading texts, which are all the reading texts in the "English for Nusantara" textbook. The results of the analysis of the Flesch Reading Ease formula, the 11 reading texts carried out by researchers in the reading texts were grouped into 4 levels, namely; easy, fairly easy, standard and fairly difficult. Of the 11 reading texts, namely easy with 1 text, fairly easy with 3 texts, standard with 4 texts and fairly difficult with 3 texts. Meanwhile, from the analysis results for the readability class, the researcher found that of the 11 reading texts, only 1 text was suitable for class VII junior high school students, namely text 5, reading text number 5 was based on the Flesch Kincaid Reading Age with a score on a scale of 7.00-7.99, which means suitable for use with class VII students.